An evaluation research on the present bachelor of science in clothing technology curriculum - Jamela, Jo Anne O.
This study is designed to know if the present Bachelor of Science in Clothing Technology (BS CT) curriculum is adequate and relevant enough to the current trends and demands in the garment industry. Specifically, this research made inquiries on the prevailing trends and demands in the garment industry to which the adequacy and relevance of the curriculum were based on. Comments and recommendation on the sequencing and time allotments of the major subjects and the suggested major and minor subjects to be added to or removed from the curriculum, were carefully determined as well throughout the research process. The respondents of the study were established through one hundred percent sampling among the second to fourth-year CT students, and convenience sampling method among the CT graduates from 1997-1999. Survey questionnaires were the primary instruments used in gathering information from the respondents. At the end of the study, results showed that the comments and recommendations for the improvement of the BS CT curriculum are being addressed to the sequencing and time allotments of the major subjects, pre-requisite subjects, elective courses, merchandising and management, textiles and production-related major courses, facilities, lecturers, and instructors of the BS CT program. The suggested revisions in these areas are hoped to aid better the program into meeting the needs of the garment industry at the on-set of globalization.